Productive Zakat: An Intertemporal Sentiment Analysis - Maliha, Hasna (Islamic Economics and History, 2023)
This study aims to measure public sentiment towards productive zakat by analyzing scientific publications from 1991 to 28 November 2023 using secondary data from the Scopus database. The research sample consists of 43 scientific publications indexed in Scopus. The results show that positive sentiment dominates with a percentage of 42%, while neutral sentiment occupies the second position with a percentage of 32%. Negative sentiment reached 26%. In the context of intertemporal analysis, 2020 recorded the highest number of sentiments throughout the period with 9 sentiments. Positive sentiment reached its highest peak in 2020 and 2021, with 4 sentiments each. Neutral sentiment reached its highest peak in 2019 and 2020, each with 3 sentiments. The year 2021 is characterized by a high number of negative sentiments, reaching 3 sentiments in that year. These findings provide an overview of the dynamics of public sentiment towards productive zakat during the study period and show the changing trends in views revealed through scientific publications